Does the presence of an opponent affect object projection accuracy in elite athletes? A study of the landing location of the short serve in elite badminton players - Vial, S.; Croft, J. L.; Schroeder, R. T.; Blazevich, A. J.; Cochrane Wilkie, J. (International Journal of Sports Science & Coaching, 2020)
The ability to accurately project (e.g. throw, kick, hit) an object at high speed is a uniquely human skill, and this ability has become a critical feature of many competitive sports. Nonetheless, in some sports, the target or end-point for a projected object is often not reached because an opponent intercepts or returns the object; thus, a player cannot use object landing location information to inform accuracy outcome. By comparing the landing location of serves performed without an opponent by elite badminton players to predicted landing points of serves delivered with an opponent, we aimed to determine whether object projection accuracy is affected by the presence of an opponent. Landing locations of serves to an opponent were predicted using a model developed through analysis of serves without an opponent present. The model predicted that 69% of serves to an opponent would have landed on or short (i.e. outside the permitted area) of the service line. Thus, serve trajectory in elite badminton players was considerably altered by the presence of an opponent, despite their aim to serve to a specific point on the court.